Primary marginal zone lymphoma of the breast; a rare case report and review of the literature - Sawsan Ismail; Haidara Kherbek; Jana Skef; Mazen Naser Eldine; Zuheir Alshehabi (Elsevier, 2020)
Primary breast lymphomas (PBLs) represent an extremely rare entity that accounts for approximately 0.38-0.7% of all lymphomas and 0.04-0.5% of all breast malignancies. Most PBL cases are of B-cell subtype of non-Hodgkin lymphomas, an and diffuse large B-cell lymphoma( DLBCL) is considered the most common histological subtype, whereas extranodal presentation of marginal zone mucosa-associated lymphoid tissue (MALT) lymphoma of the breast represents an exceedingly rare entity.We report the case of a 55-year-old Syrian female who presented to our hospital due to a painful palpable mass in her left breast. Clinical and radiographic findings were highly suggestive of breast carcinoma. Therefore, an excisional biopsy was performed, and interestingly; histological examination revealed the diagnosis of primary breast lymphoma, and Immunohistochemical examination confirmed the diagnosis of a marginal zone lymphoma of (MALT) type of the breast.Herein, we aimed to present a hard-challenging case that highlights the rarity of presentation of primary lymphomas in the breast, as well as the difficulties in the differential diagnosis of lymphoid neoplasms. Furthermore, we aimed to present a brief review of diagnostic methods, detailed examination and treatment recommendations.